The Role of Penta Helix in Implementing Zero Hunger (Case Study: Social Project “Fight Hunger to Achieve Our Better Future”) - Januari Pratama Nurratri Trisnaningtyas; Raden Diman Satria Juliartha; Ariesa Maryam Kusuma; Maulana Muhammad Daffa (Nusantara Science and Technology Proceedings, 2022)
Food security has become a prominent issue within sustainable development goals. The high number stunting and malnutrition in Indonesia proves that the zero hunger of SDGs has not been optimally achieved. The government and community face various challenges to end hunger, such as economic limitation and access to the nutritious and sufficient food. This paper will examine how to tackle food security in Indonesia by implementing “Fight Hunger to Achieve Our Better Future” Project. This project was initiated by student of International Relations Department of UPN “Veteran” Jawa Timur as a project-based study of Sustainable Development. Using the concept of sustainable development and food insecurity as well as penta helix model, there are three series of activities carried out to contribute in ending hunger in Indonesia, namely catfish farming, food security seminar and webinar series, and petition signing. The project successfully involving 350-400 people consist of local communities, village government, high school and university students, medium-small enterprises (UMKM) and media to support zero hunger campaign. This paper argue that the involvement of the penta helix actors would perform better to achieve food security in Indonesia, which included in the SDGs number two.